1983
DOI: 10.1172/jci110866
|View full text |Cite
|
Sign up to set email alerts
|

Iron and the liver: acute effects of iron-loading on hepatic heme synthesis of rats. Role of decreased activity of 5-aminolevulinate dehydrase.

Abstract: A B S T R A C T Acute iron loading of rats, by intraperitoneal administration of iron-dextran (500 mg Fe/kg body wt 18-20 h before killing) decreased by 30% the rate of conversion of 5-amino-['4Cllevulinate (['4C]ALA) into heme as measured with a recently described procedure for liver homogenates (1981. Biochem. J. 198: 595-604). The decrease in conversion of labeled ALA into heme caused by iron loading was shown to be due to a 70-80% decrease in activity of ALA dehydrase. The decrease in activity of ALA dehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
6
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 18 publications
3
6
0
Order By: Relevance
“…While the reduction of ALA dehydratase activity had no effect on ALAS-E in bone marrow cells, mRNA for ALA dehydratase and ALAS-N in bone marrow cells were increased to 1.6-times and 3.7-times the control, respectively. It has also been reported that a 70% to 80% reduction in ALA dehydratase activity caused by acute iron loading in rats leads to a 30% decline in heme synthesis [66]. Although ALA dehydratase activity is 100-times greater than ALA synthase activity in normal tissues, these observations suggest that inhibition of ALA dehydratase may become a rate-limiting step of heme synthesis not only in the liver but also in erythroid cells, and in certain conditions that clinically mimic acute hepatic porphyria [60].…”
Section: Decreases In Ala Dehydratase Activity By Chemicals and Effecmentioning
confidence: 95%
“…While the reduction of ALA dehydratase activity had no effect on ALAS-E in bone marrow cells, mRNA for ALA dehydratase and ALAS-N in bone marrow cells were increased to 1.6-times and 3.7-times the control, respectively. It has also been reported that a 70% to 80% reduction in ALA dehydratase activity caused by acute iron loading in rats leads to a 30% decline in heme synthesis [66]. Although ALA dehydratase activity is 100-times greater than ALA synthase activity in normal tissues, these observations suggest that inhibition of ALA dehydratase may become a rate-limiting step of heme synthesis not only in the liver but also in erythroid cells, and in certain conditions that clinically mimic acute hepatic porphyria [60].…”
Section: Decreases In Ala Dehydratase Activity By Chemicals and Effecmentioning
confidence: 95%
“…In earlier work effects of experimental iron overload on hepatic heme metabolism and hemoproteins have been described, including decreased cytochrome P-450'; increased 5-aminolevulinate (ALA)' synthase,'q2 heme ~x y g e n a s e ,~ and rates of hepatic heme breakdown4; and transiently decreased ALA dehydrase. 2 The feeding of carbonyl-iron to rats provides a new model of hemochromatosis (HC) with features resembling human primary HC more closely than those used previo~sly.~ In these experiments we studied effects of iron loading with enteral carbonyl-iron on hepatic ALA dehydrase.…”
Section: Introductionmentioning
confidence: 99%
“…Several reported effects of iron on hepatic heme metabolism could help to account for its effect in PCT, including inhibition of the formation or decarboxylation of uroporphyrinogen 111, the former by inhibition of uroporphyrinogen I11 cosynthase (12) and the latter by inhibition of uroporphyrinogen decarboxylase (13, 14). However, it has also been reported that iron ions do not affect (15,16) or activate (17) the decarboxylase, and iron loading of rats by enteral (18) or parenteral (19) iron administration did not produce changes in activity of uroporphyrinogen decarboxylase.…”
mentioning
confidence: 96%
“…Iron-stimulated depletion of a regulatory heme pool in hepatocytes may also play a role, since such depletion would increase activity of 5-aminolevulinate (ALA) synthase, normally the rate-controlling enzyme for hepatic heme synthesis (I), and thus increase the formation of uroporphyrinogen that might be oxidized to uroporphyrin. It is likely that iron can deplete a regulatory hepatic heme pool since iron (a) increases rates of hepatic heme degradation (22), (b) increases activity of hepatic heme oxygenase (23)(24)(25)(26) and (c) decreases concentrations of hepatic microsomal total and cytochrome P-450 heme (19,23,25,(27)(28)(29) in association with lipid peroxidation (26). Increased activity of hepatic ALA synthase (19) and synergism of drugmediated induction of t h e synthase (28)(29)(30)(31), afford further support for an effect of iron t o deplete a regulatory heme pool in the liver.…”
mentioning
confidence: 99%